The Land Law Reform in the Philippines State - Aquilino Aquilino (JURNAL AKTA, 2022)
This research aim to know the land reform in the Philippines has long been a contentious issue rooted in the Philippines's Spanish Colonial Period. Some efforts began during the American Colonial Period with renewed efforts during the Commonwealth, following independence, during Martial Law and especially following the People Power Revolution in 1986. This research used the qualitative with normative approach especially the regulation of Land in Philippines. The current law, the Comprehensive Agrarian Reform Program, was passed following the revolution and recently extended until 2014. Much like Mexico and other Spanish colonies in the Americas, the Spanish settlement in the Philippines revolved around the encomienda system of plantations, known as haciendas. As the conclusion explained that in the 19th Century progressed, industrialization and liberalization of trade allowed these encomiendas to expand their cash crops, establishing a strong sugar industry in the Philippines, especially in the Visayan island of Negros.